Park Sculpture of the Kuskovo Estate: Current Problems of Study and Restoration - Shumilova, Khristina V.; Schedrova , Olga V. (Actual Problems of Theory and History of Art, 2023)
The article deals with the fate of a unique collection of sculpture by Italian masters of the mid-second half of the 18th century, which reflects the specifics of the attitude towards decorative park sculpture. Modern restoration methods require careful attention to the study of material related to the history of the existence of monuments. During the heyday of the ensemble, it was taken care of by preventive conservation measures. During the hostilities of 1812, the sculpture suffered from acts of vandalism. After the WWII, the park went through a significant stage of restoration, when the sculpture was removed from the basements of the palace. Unfortunately, in the following years the monuments were exposed to increasingly aggressive environmental influences and again suffered from the hands of vandals. Systematic and planned restoration work began in the mid-1950s, with an important stage in the history of the existence of sculptures being the works carried out since 1998 by employees of the Grabar Art Conservation Center. In 2019, the Kuskovo Museum-Estate celebrated its 100th anniversary, and the works on a comprehensive large-scale restoration of the park sculpture were timed to coincide with this event. Nowadays, the practice of museumification of the originals and replacing them with casts does not resolve the problem of the restoration of monuments, which gains particular significance. In Kuskovo, sixty-four monuments were restored, twenty of which were replaced with copies. The copies were made of polyester resin with a high concentration of marble chips, tinted to match the surface color of the original busts. A comparative analysis of archival photographic material and the current state of preservation indicates the loss of the original surface of most of the sculptures and the presence of numerous traces of anthropogenic impact, which had to be taken into account when carrying out the work. As a result of the joint work of restorers and museum staff, the monuments acquired an exposition appearance: their condition has been stabilized, sculptures requiring more careful monitoring have been identified, and a further care program has been developed. The field and laboratory studies, as well as the work with archival materials, made it possible to clarify the attribution of the objects and to fill some gaps in the history of the existence of the monuments.
Keywords: Kuskovo; sculpture of the 18th century; restoration; history of existence; copy; conservation; museum